Active methodologies in engineering teaching: a bibliometric review - Valença, Antonio Karlos Araújo (2023)
This article presents a bibliometric review on the use of active methodologies in engineering education. The study aimed to analyze the existing scientific production on this topic, identifying research trends, areas of study and contributions. We reviewed forty-one studies published in relevant scientific journals. The review revealed that active methodologies such as Problem-Based Learning, Project Learning and Flipped Classroom are regular used in engineering education, with a growing interest in recent years. In addition, research trends were identified, such as the use of digital technologies and software development that would engage the learning and academic performance of engineering students. Based on the bibliometric results, the courses that stood out the most were Production Engineering and Computer Engineering with six papers published each. The research findings highlight the importance of these approaches to promote more effective training, preparing engineering students to meet the challenges of the contemporary world.